Daratumumab plus lenalidomide, bortezomib and dexamethasone in newly diagnosed multiple myeloma: Analysis of vascular thrombotic events in the GRIFFIN study. (16th September 2022) - Sborov, Douglas W.; Baljevic, Muhamed; Reeves, Brandi; Laubach, Jacob; Efebera, Yvonne A.; Rodriguez, Cesar; Costa, Luciano J.; Chari, Ajai; Silbermann, Rebecca; Holstein, Sarah A.; Anderson, Larry D.; Kaufman, Jonathan L.; et al.
Summary: Patients with multiple myeloma are at increased risk of vascular thromboembolic events (VTEs). This post hoc analysis evaluated VTEs in the randomised phase 2 GRIFFIN study (ClinicalTrials.gov Identifier: NCT02874742) that investigated lenalidomide/bortezomib/dexamethasone (RVd) ± daratumumab (D). Patients with newly diagnosed multiple myeloma who were eligible for autologous stem cell transplantation (ASCT) received D‐RVd/RVd induction, high‐dose therapy and ASCT, D‐RVd/RVd consolidation and up to 2 years of lenalidomide maintenance therapy ± D. VTE prophylaxis was recommended (at least aspirin, ≥162 mg daily) in accordance with International Myeloma Working Group guidelines. In the safety population (D‐RVd, n  = 99; RVd, n  = 102), VTEs occurred in 10.1% of D‐RVd patients and 15.7% of RVd patients; grade 2–4 VTEs occurred in 9.1% and 14.7%, respectively. Median time to the first onset of VTE was longer for D‐RVd versus RVd patients (305 days vs 119 days). Anti‐thrombosis prophylaxis use was similar between arms (D‐RVd, 84.8% vs RVd, 83.3%); among patients with VTEs, prophylaxis use at time of first VTE onset was 60.0% for D‐RVd and 68.8% for RVd. In summary, the addition of daratumumab to RVd did not increase the incidence of VTEs, but the cumulative VTE incidence was relatively high in this cohort and anti‐thrombotic prophylaxis use was suboptimal.